Does moderate intensity impact exercise and non-impact exercise induce acute changes in collagen biochemical markers related to osteoarthritis? – An exploratory randomized cross-over trial. Issue 7 (July 2021) - Bjerre-Bastos, J.J.; Nielsen, H.B.; Andersen, J.R.; Karsdal, M.; Bay-Jensen, A.-C.; Boesen, M.; Mackey, A.L.; Byrjalsen, I.; Bihlet, A.R.
Summary: Objective: To investigate acute changes in biochemical markers of cartilage turnover in response to moderate intensity exercise with and without joint impact in humans with knee osteoarthritis. Design: We conducted a randomized, cross-over, exploratory clinical study. Twenty subjects with knee osteoarthritis (OA) were randomized, of which twenty completed 30 min of cycling and 15 completed 30 min of running on days 1 week apart. Fasting blood samples were taken before, immediately after and 1, 2, 3, and 24 h after activity was initiated. Midstream spot urine was sampled before and after activity. Serum samples were analyzed for concentrations of fragment of type II collagen degradation, C2M, fragment of type VI collagen degradation, C6M, cartilage oligomeric matrix protein, COMP, marker of type II collagen formation, PRO-C2, and urine for marker of crosslinked type II collagen degradation, CTX-II. To establish a reference, all subjects had similar samples taken during rest on a separate day. Data was analyzed in a restricted maximum likelihood based random effects linear mixed model. Results: C2M trended to increase after cycling compared running (13.49%, 95%CI: −0.36–27.34%) and resting (12.88%, 95%CI: 0.2–25.6%) and the type II collagen formation/degradation ratio switched towards degradation after cycling, but not running. C6M trended to decrease after cycling (−8.1%, 95%CI: −14.8 to −1.4%) and running (−6.8%, 95%CI: −14.16–0.55%). Conclusion: In persons with knee OA moderate intensity exercise without joint impact may induce acute changes in circulating levels of biochemical markers reflecting type II and VI collagen degradation.